Integrating PID Control and Emergency Protection in Natural Gas Processing: A Theoretical Framework with Emphasis on Modeling and Optimization Techniques - Nasser, Sabreen H.; Al-Radhi, Mohammed S. H. (Journal of Petroleum Research and Studies, 2025)
This study introduces new advancements in natural gas treatment processes post-extraction from oil wells, emphasizing dynamic modeling and control experiments for improved efficiency and safety. Addressing the challenges of gas with high oil content exposed to extreme conditions during extraction, our research employs a state-of-the-art PID control system. The PID system uniquely allocates the proportional integral component exclusively for gas level control, while both components regulate pressure and temperature. Complemented by an advanced emergency protection system, featuring a precision pressure relief valve and automatic shutdown switch, our control mechanisms are evaluated alongside other types, including state space and adaptive controllers. The proposed PID controller emerges as optimal, continuously adjusting output based on the discrepancy between desired and actual outputs. Beyond control strategies, the study highlights the transformative impact of gas processing, converting raw natural gas properties into methane. The findings have significant implications for the gas processing industry, offering improved operational efficiency, enhanced safety measures, and a reduced environmental footprint. By showcasing groundbreaking advancements in dynamic modeling and control experiments, this research paves the way for future innovations, pushing the boundaries of natural gas processing system optimization